Factors Influencing Students' Perceptions of Their Teachers' Interpersonal Behaviour: A Multilevel Analysis - Fisher, Darrell; Den Brok, P.; Rickards, Anthony (World Scientific Publishing, 2006)
This chapter describes a study in which student, teacher and class characteristics• were associated with students’ perceptions of their teachers' interpersonal behaviour. Using the Questionnaire on Teacher Interaction (QTI). two important dimensions of teacher interpersonal behaviour were investigated: influence (dominance vs. submission) and proximity (cooperation vs. opposition). Earlier work with the QTI in the USA and the Netherlands has shown that, in those countries, several factors affect students' perceptions of their teachers. These factors include student and teacher gender, student and teacher ethnic background, student age, teacher experience, class size, student achievement and subject. It has been found that each of these variables has a distinctive effect, but also that they interact with each other when determining students' perceptions. In this study, a meta-analysis was performed on a large Australian secondary student and teacher QTI data set. QTI dimension scores were examined against factors such as: gender, class size and subject. To investigate separate and combined effects of variables, a hierarchical analysis of variance (distinguishing between the school, class and student level) was conducted with ML3E software. This chapter discusses the effect sizes and variance explained by these variables.